Pengaruh Strategi Servo Analisis Terhadap Kinerja Bank Syariah Indonesia KCP Purwokerto Karangkobar - Aliyah, Fatmah Nur; Maulana, Mohamad Riski; Fardah, Salsabila Destria; Shafrani , Yoiz Shofwa (Universitas Maritim AMNI Semarang, 2025)
Competition within Indonesia's banking landscape, specifically at BSI KCP Purwokerto Karangkobar, necessitates flexible strategies to stay relevant. This research assesses how the utilization of SERVO (Strategy, Environment, Resources, Value, Organization) analysis impacts the performance of the firm. Employing qualitative descriptive techniques, information was gathered through comprehensive interviews, observations, and document reviews. Results reveal that strategies focusing on digital advancement, community engagement, and operational effectiveness are vital components. Cooperation among departments, particularly between gold services and microfinance, fosters social bonds and enhances transparency. The teller and security teams uphold service excellence through the consistent application of Standard Operating Procedures. The SERVO framework has shown to be effective in merging digital advancements with sharia principles within company operations, which enhances customer satisfaction and boosts competitiveness. Proactive modifications in response to evolving customer demands are essential for enhancing institutional effectiveness.